High variability of Panton-Valentine Leukocidine producing methicillin-resistant Staphylococcus aureus isolated from skin and soft tissue infections in the province of Bolzano - Richard Aschbacher; Bruno Pichon; Greta Spoladore; Elisabetta Pagani; Patrizia Innocenti; Ludwig Moroder; Renate Meyer; Brigitte Ladinser; Mark Ganner; Robert Hill; Rachel Pike; Oswald Ganthaler; et al. (Microbiologia Medica, 2012)
Introduction. Panton-Valentine leukocindin (PVL) positive community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) isolates are widespread in many countries, with varying distribution and epidemiology. The aim of this study was to characterise the ten PVL positive MRSA isolates collected during February 2010 to January 2011 from skin and soft tissue infections in the North Italian Province of Bolzano. Methods. Accessory gene regulator (agr) typing, staphylococcal cassette chromosome (SCC) mec typing, spa typing,multi-locus sequence typing (MLST), toxin gene profiling, PCR for type I arginine catabolic mobile element (ACME) and antimicrobial resistance typing were applied to the isolates. Results. Eight different CA-MRSA clones were identified: ST30-IVc, ST772-V, ST80-IVc, ST5-IVc, ST88-IVa, ST93- IVa, ST8-IVc and the type I ACME positive ST8-IVa. Conclusions. The high heterogeneity of PVL-positive MRSA probably reflects the introduction of different clones by international travellers or immigrants.